Pengaruh Pendekatan Pembelajaran Realistic Mathematics Education (RME) terhadap Minat dan Hasil Belajar Matematika - Luh Catrining; I Wayan Widana (FPMIPA IKIP PGRI Bali, 2018)
This study aimed to determine the effect of Realistic Mathematics Education (RME) approach to the interest and outcomes of mathematics learning of seventh grade students in SMP Negeri 6 Denpasar academic year of 2017/2018. The type of research was a quasi experiment and the design of research was non equivalent posttest-only control group design. The population were 9 classes of seventh grade students (364 students) in SMP Negeri 6 Denpasar which involved 2 classes as the sample taken by using simple random sampling technique. The obtained data of this research used questionnaire and mathematics test score which furthermore analyzed by using MANOVA with SPSS 22.0 for Windows. Based on the obtained hypothesis test results: 1) there were difference in the interest of learning between students joined the Realistic Mathematics Education approach with students who joined the conventional learning approach, with the value 0,000 < 0,05, 2) there were difference in the mathematics learning outcomes between students joined the Realistic Mathematics Education approach with students who joined the conventional learning approach, with the value 0,047 < 0,05 and 3) there are simultaneous difference of the interest and outcomes of mathematics learning between students who joined the Realistic Mathematics Education approach with students who joined the conventional learning approach, with the value 0,001 < 0,05. So there are an effect of Realistic Mathematics Education approach to the interest and outcomes of mathematics learning.